(3JPcQI GdeMJGL Edi CMGOjK GdefgGL aj GdCUhds - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s
(3ChdgG (B:s
(3agPG JYdjb fGaY Ef TGA Gddg JYGdi Ydi GdCMGOjK hGdBKGQ GdhGbYI ai efgGL GdCUhd ddbGVi fGUQ GdOjf GdHjVGhi s
(3BNQgG (B:s
(3hGab JYdjbg jhe GdNejS SGOS YTQ ef ThGd GdecQe SfI NeS hNeSjf hSHYeGFI s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B57s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1879s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs